Digital Divide among Social Sciences Faculty and Researchers in Selected Universities of Punjab and Chandigarh - Dr. Harvinderjit Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The study is focused on identifying digital divide among Social Sciences faculty and researchers in the universities of Punjab and Chandigarh. This study is a survey based study in which questionnaire method was used to collect the data from respondents. The data were analyzed and tested using different statistical techniques. This study has found that Social Sciences faculty and researchers were having the awareness of web-based resources and services, ability to use them and their overall use by them was found to be ‘to some extent’. Moreover there was a significant difference between the Social Sciences faculty and researchers related to their awareness, ability and use of web-based resources and services..